A Group Portrait of “Media War Criminals” - Reljić, Slobodan (Sociološki pregled, 2020)
This is a opinion / review of Slobodan Vuković’s book that provides 1) a detailed overview of how Western media reported on the war in the SFR Yugoslavia, and 2) meaningful synthesis that confronts the reader with the nature of this local conflict with global ramifications.